Makna Psikologis dan Teologis Keberadaan Manusia Menurut Lukas 10:27 - Zevania Venda Andaline (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2019)
The difference in viewpoints between dichotomous and trichotomic understandings will certainly not subside. The dichotomous believer has an emphasis on the visible and invisible. On the other hand, those who want to describe human existence in more detail are often called trichotomists. Yet if you want to sort out the existence of humans will be more than just 3 parts.